Speak Camfranglais pour un Renouveau Onglais - Vakunta, Peter W. (Book collections on Project MUSE., 2014)
The poems in this collection are a mirror reflecting the goings-on in the nooks and crannies of the Republic of Cameroon. Crafted in the lingo of the man in the street, these poems speak for the voiceless in Cameroon, for all those who live on the fringe of a rich Cameroonian society. The themes broached are numerous, namely the culture of impunity, the vicious cycle of corruption, abuse of power, influence peddling, rape of the constitution, electoral gerrymandering, and the ineptitude of national bourgeoisie to name but a few. In sum, Speak camfranglais pour un renouveau ongolais is a clarion call for a new deal in Cameroon.